2014
DOI: 10.2514/1.j053018
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Aeroelastic and Aerothermoelastic Studies Using Computational Fluid Dynamics

Abstract: A framework for aerothermoelastic-stability-boundary calculation for hypersonic configurations using computational fluid dynamics combined with radial basis functions for mesh deformation is developed. Application of computational fluid dynamics enables one to consider different turbulence conditions, laminar or turbulent, and different models of the air mixture, in particular real-gas model, which accounts for dissociation of molecules at high temperature. The effect of transition on the flutter margin of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…(15). Noting the relationship between derivatives of the two planes, the Euler equations as written in the z-x plane Eqs.…”
Section: A Piston Analogymentioning
confidence: 99%
See 1 more Smart Citation
“…(15). Noting the relationship between derivatives of the two planes, the Euler equations as written in the z-x plane Eqs.…”
Section: A Piston Analogymentioning
confidence: 99%
“…However, piston theory enjoyed renewed attention in the 1990s, with the early implementation of piston theory with Euler solutions in CFD [8] and with continued development of aeroelastic panel codes [9]. The 2000s saw a marked resurgence in the interest in piston theory as a computationally inexpensive method for modelling supersonic and hypersonic aeroelastic problems, with applications being found in aeroservo-elasticity and aero-thermo-elasticity, with the further integration of piston theory with CFD; recent literature highlights the continued application of piston theory in reducing the computational cost of CFD for hypersonic aeroelasticity [10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…Whereas the early research was instrumental in providing the basis for the aerothermoelastic design of the X-15 and the space shuttle [3][4][5], the current focus is on the development of hypersonic technologies for next-generation reusable launch vehicles and hypersonic cruise vehicles [6][7][8]. Current research includes: development of reduced order models for aerothermoelastic systems [9,10], structural optimisation [11], uncertainty propagation [12,13], coupling CFD with aerothermoelastic models [14], two-dimensional nonlinear flutter models [15] and three-dimensional flutter models [16]. This work has shown that the dynamic behaviour of the structure under the harsh thermal environment must be investigated for hypersonic aircraft to become a reality.…”
Section: Introductionmentioning
confidence: 99%
“…At hypersonic speeds, aerodynamic heating leads to extremely high heat flow and temperature on the outer surface of the machine and in the channel of the hypersonic propulsion air-jet engine [1]. A well-designed thermal protection system must maintain the integrity of the aircraft, preventing the thermal loads.…”
Section: Introductionmentioning
confidence: 99%
“…Security, viability and stability are key considerations in achieving the goals of the flight. For their achievement, the knowledge of temperatures and heat flows for creation of effective thermal protection system [1,2] is required.…”
Section: Introductionmentioning
confidence: 99%